The main online newspapers in Spanish: the development of commercial services - Albornoz, Luis A. (FCL-UNESP Laboratório Editorial, 2007)
The present article contains the results of a recent PhD investigation – entitled “The online general information newspapers. The case of the main periodicals in Spanish” (April 2005) – related to online commercial services of some of the main electronic periodicals in the Spanish language: ElMundo.es, Clarín.com, Reforma.com, ElPaís.es, Abc.es and La Nación Line.